2021
DOI: 10.1007/s10035-021-01087-5
|View full text |Cite
|
Sign up to set email alerts
|

Meso-scale signatures of inertial transitions in granular materials

Abstract: Granular materials have a complex collective behavior based on simple interactions between grains. The global behavior stems from dynamic rearrangements in the micro-structure. The local increase (resp. decrease) of the density generates jamming (resp. unjamming). In this paper, instabilities in the form of localized bursts of kinetic energy are studied at both the micro-scale (i.e. grain scale) and meso-scale (i.e. cluster scale). The bursts are defined from the variation of kinetic energy. The meso-domains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…5, where a biaxial loading path is simulated by using a discrete element method, stress fluctuations develop after the stress peak is reached, and become well marked in the critical state regime. As pointed out in Zhu et al (2016b) and Clerc et al (2021), these stress fluctuations stem from continuous microstructural reorganizations occurring within the assembly. Considering the evolution of two loop categories (loops with 3 grains, and loops with 6 grains), it can be observed in Fig.…”
Section: Stationary Regime and Fluctuationsmentioning
confidence: 82%
“…5, where a biaxial loading path is simulated by using a discrete element method, stress fluctuations develop after the stress peak is reached, and become well marked in the critical state regime. As pointed out in Zhu et al (2016b) and Clerc et al (2021), these stress fluctuations stem from continuous microstructural reorganizations occurring within the assembly. Considering the evolution of two loop categories (loops with 3 grains, and loops with 6 grains), it can be observed in Fig.…”
Section: Stationary Regime and Fluctuationsmentioning
confidence: 82%
“…While granular gases are better described by kinetic theory [5], dense granular fluids and granular solids are much harder to understand, in particular since they can transit from fluid-like flowing states to static, reversibly elastic states, dependent on the inflow and dissipation of energy. How and why they achieve this transition is still under debate, e.g., by irreversible plastic deformations [16][17][18][19][20][21][22][23][24][25], related also to creep/relaxation [11,[26][27][28], and many other studies, see Ref. [29] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…While slow shear shows evident stress drops due to mesoscale re-arrangements and deformations, see Refs. [21, [23][24][25], it was reported that there is only much weaker action under isotropic deformations in a small density window [21] for non-spherical, frictional particles. However, for frictionless spheres, a lot of re-arrangements are possible [4,6] and visible if only the compression rate is slow enough.…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish shear bands from local shear patterns in frictional granular materials, an intermediate scale, i.e., meso scale, between grain and sample scales is needed. At this scale, slip structures can be analyzed from both continuum and discrete points of views, provided that local stresses and strains are consistently defined [49][50][51].…”
Section: Introductionmentioning
confidence: 99%